Conceptions of sexuality of adolescents living in residence cares: are their interests and curiosities different? - Anastácio, Zélia (2021)
The institutionalization of children and adolescents generally is due to unfavourable socio economic conditions, children maltreatment, school absenteeism and adolescents’ behavioural problems, including sexual risk behaviours. Sexuality education (SE) is very difficult to approach in residence care, given the sensitive and problematic life stories of adolescentes involved. It is important to know what adolescents already know and what they want to learn and clarify about sexuality. The research question was: What interests and curiosities of sexuality do adolescents living in residence care have? The objectives were to make a diagnosis of adolescents’ interests, needs and conceptions about sexuality and to relate these conceptions with individual factors. A transversal study was done following a quantitative methodology. A questionnaire was carried out for this research. Dependent variables were: sources of information about SE; perceptions about the role of SE on children and adolescents’ development; responsible intervener for SE; sexuality topics about which adolescents want to learn more. A convenience sample included 114 teens aged between 11 to 21 (mean=15.7±2.4; 68 females and 46 males), living 60,5% of them since more than 24 months ago in residence care. A statistical analysis was done. Results showed that in adolescents’ views, the main role of SE is: to help them to respect different sexual orientations; to understand that sexuality expresses differently along the lifespan; and to promote equal rights and opportunities between men and women. Their main sources of information are friends, internet and familiars with approximately equal age. Persons they consider to be most responsible for their SE are doctors, nurses and mothers, with significant differences for health professionals, girls having a higher preference for them than boys. Topics about which adolescents have more interest and curiosity are: love, friendship and romantic relationships; adolescence; diversity, tolerance, sexual orientation and respect; and sexually transmitted diseases and infections.